Association of Iron Deficiency Anemia with Pneumonia in 6 Months to 5 Years Old Children - Akther, Naima; Ghosh, Uzzal Kumar; Sufian, Abu; Hafiz, Faeqa; Banu, Nazneen Akhter; Bhuiyan, Md Moniruzzaman; Islam, Tithi (Eastern Medical College Journal, 2023)
Background: Pneumonia is the leading cause of childhood death under five years old in developing countries. Anemia is the commonest ailment affecting health, socio-economic development and the overall betterment of mankind. This study was conducted to determine the association between iron deficiency anemia (IDA) and pneumonia in the age group 6 months to 5 years. Methods: A cross-sectional analytical study was conducted in the Department of Pediatrics, SSMC & Mitford Hospital. According to selection criteria, 64 patients with pneumonia were considered as cases and matched 64 patients with fever and cough and but having no pneumonia, participated as control. Chest X-ray and complete blood count with RBC indices, iron profile was done to see pneumonia and IDA. A comparison was done between two groups. p-value was significant when < 0.05. Results: The mean age was 18.65±16.43 months in the case group and 14.17±10.76 months in the control group. Male was found 65.6% in the case and 73.4% in the control group. Females were 34.4% in the case and 26.6% in the control group. No significant difference in age and sex between the two groups. Decreased level of Hb, RBC, MCV, MCHC & increase RDW and also decreased level of serum iron, ferritin, transferrin & increased TIBC in the case group; all of which were statistically significant when compares to the control group. IDA was 65.6% in the case group; 17.2% in the control group. IDA was significantly higher in the case group compared to the control group. Conclusion: Sixty-six percent of children of 6 months to 5 years of both sexes with pneumonia associated with IDA. So, Iron deficiency anemic child more risk of developing pneumonia. EMCJ. July 2022; 7(2): 10-15